NASA in the World - Krige, John. author. aut Link
XVII, 353 p. 5 illus.
Keywords: Since its inception, NASA has participated in over 4,000 international projects, yet historians have almost entirely neglected this remarkable aspect of the agency's work. This groundbreaking work is the first to trace NASA's history in a truly international context, drawing on unprecedented access to agency archives and personnel.